Pentingnya Pemahaman Orang Tua tentang Karakteristik Pembelajaran AUD dalam Penerapan Model Environmental Print Berbasis Keluarga untuk Meningkatkan Kemampuan Membaca Awal Anak - Ismaniar, Ismaniar; Jamaris, Jamaris; Wisroni, Wisroni (Universitas Negeri Padang, 2018)
The low development of early reading ability in early childhood can be caused by many factors, one of which is due to lack of stimulation from the family environment. The role of the family environment becomes very important, because both quantity and quality of the presence of children are spent more in the family. The family-based environmental print model is an innovation that can be used in stimulating early reading skills in children in the family. To be able to obtain optimal results in the use of this model, parents must understand the characteristics of early childhood learning. A correct parent's understanding of the characteristics of children's learning can make the stimulation process take place pleasantly, according to the child's learning style without any element of coercion from parents to children. In addition, the active role of parents can also be done with the right portion of the sign of showing an uncaring attitude or just letting go of the extraction of children's interest in media and conditions that have been prepared using the environmental print model.Key Word: Parental Understanding, Characteristics, Learning, Early Reading, Environmental Print